A systematic analysis of deuteron breakup. (10th March 2023) - Torabi, F; Carlson, B V
Abstract: Inclusive breakup cross sections for deuterons incident on a wide range of nuclei at different incident energies are studied. In our analysis, we use the post-form distorted-wave-Born approximation (DWBA) to calculate the elastic and nonelastic breakup cross sections. We also calculate exciton and statistical compound-nucleus model cross sections to account for pre-equilibrium and equilibrium emissions. The calculations are performed using the code EMPIRE and are compared to the available experimental data. The comparisons of the integrated cross sections reveal a generally good agreement between the calculations and the data. However, systematic discrepancies are observed between the calculated double differential neutron and proton cross sections and the data, especially for heavier targets. Possible reasons for the disagreements between the theoretical predictions and the experimental data are discussed.